Pengembangan Model Manajemen Bengkel (Workshop) Pemesinan Politeknik Menjadi Berkarakter Keselamatan Dan Kesehatan Kerja (K3) - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Bambang Kuswanto (Teknis, 2015)
Accident figures working in the industry last year in the initial on symptoms enough worrying rise. One of the causes of workplace accidents are caused by human posted or workers. It seems the problem initials national problem being should operate together find a solution. Polytechnic as prayer one thing to prepare candidate labor for industries, is expected to contribute the real at resolution initials. Development management Â machine workshop model being a character K3, expected may create conditions and a safety working environment.Â Efforts to establish the initial conditions of a student character for any care and always run the work that they do pay attention seriously Safety and Health . If the husband habits are formed so expected successful inÂ alumni of the Polytechnic of being the character K3 workers in the industry.Keywords: Accidents, management model, K3 Character